Investigation the structured material surfaces using the quartz tuning fork based on an atomic force microscopy with controllable q-factor in two modes operation: “intermittent contact” and “shear-force” - Vo Thanh Tung; Chizhik, S.A.; Chikunov, V.V.; Tran Xuan Hoai (Науковий фізико-технологічний центр МОН та НАН України, 2008)
We present a combination of an atomic force microscopy with a quartz-crystal tuning fork in ambient conditions. A silicon cantilever tip was attached to one prong of the tuning fork to realize shear-force and intermittent contact mode Fork-AFM operation. By electronically adjusting the quality factor of the probe, called Q-control, it was possible to tune the quality factor Q and correspondingly change the overall scanning time. It was also seen that tuning fork with low quality factors could increase stability with the changed signal and so improve the imaging resolution. Measurements on the different samples were used to demonstrate this technique. У роботі описується конструкція атомносилового мікроскопа c датчиком у вигляді камертона на основі кварцового кристала. Кремнієве кантилеверне вістря було закріплено до зубця камертона таким чином, що дозволило реалізувати для камертонового АСМ латерально-силовой (shear-force) і напівконтактний (іntermіttent contact) режими. За допомогою системи електронного регулювання добротності зонда, так називаного Q-контролю, можливе настроювання параметра добротності Q і, відповідно, зміна повного часу сканування. Було помічено, що шляхом зменшення параметра добротності можна збільшити стабільність вимірюваного сигналу й у такий спосіб поліпшити розподіл для формованих зображень. Для демонстрації методики використовувалися зразки різних типів. В работе описывается конструкция атомносилового микроскопа c датчиком в виде камертона на основе кварцевого кристалла. Кремниевое кантилеверное острие было закреплено к зубцу камертона таким образом, что позволило реализовать для камертонного АСМ латерально-силовой (shear-force) и полуконтактный (intermittent contact) режимы. С помощью системы электронного регулирования добротности зонда, так называемого Q-контроля, возможна настройка параметра добротности Q и соответственно изменение полного времени сканирования. Было замечено, что путем уменьшения параметра добротности можно увеличить стабильность измеряемого сигнала и таким образом улучшить разрешение для формируемых изображений. Для демонстрации методики использовались образцы различных типов.